Endothelial Monocyte-Activating Polypeptide-II Induces BNIP3-Mediated Mitophagy to Enhance Temozolomide Cytotoxicity of Glioma Stem Cells via Down-Regulating MiR-24-3p - Zhang, Jian; Liu, Libo; Xue, Yixue; Ma, Yawen; Liu, Xiaobai; Li, Zhen; Li, Zhiqing; Liu, Yunhui (Frontiers in Molecular Neuroscience, 2018)
Preliminary studies have shown that endothelial-monocyte-activating polypeptide-II (EMAP-II) and temozolomide (TMZ) alone can exert cytotoxic effects on glioma cells. This study explored whether EMAP-II can enhance the cytotoxic effects of TMZ on glioma stem cells (GSCs) and the possible mechanisms associated with Bcl-2/adenovirus E1B 19 kDa protein-interacting protein 3 (BNIP3)-mediated mitophagy facilitated by miR-24-3p regulation. The combination of TMZ and EMAP-II significantly inhibited GSCs viability, migration and invasion, resulting in upregulation of the autophagy biomarker microtubule-associated protein one light chain 3 (LC3)-II/I but down-regulation of the proteins P62, TOMM 20 and CYPD, changes indicative of the occurrence of mitophagy. BNIP3 expression increased significantly in GSCs after treatment with the combination of TMZ and EMAP-II. BNIP3 overexpression strengthened the cytotoxic effects of EMAP-II and TMZ by inducing mitophagy. The combination of EMAP-II and TMZ decreased the expression of miR-24-3p, whose target gene was BNIP3. MiR-24-3p inhibited mitophagy and promoted proliferation, migration and invasion by down-regulating BNIP3 in GSCs. Furthermore, nude mice subjected to miR-24-3p silencing combined with EMAP-II and TMZ treatment displayed the smallest tumours and the longest survival rate. According to the above results, we concluded that EMAP-II enhanced the cytotoxic effects of TMZ on GSCs’ proliferation, migration and invasion both in vitro and in vivo.